A Case Report of New-Onset Atrial Fibrillation in a Young Male After Electrical Injury - Herick Alvenus Willim; Harie Cipta (HM Publisher, 2022)
Electrical injuries occur mostly as a consequence of home or workplace accidents. It can cause various manifestations from minor skin burn injuries to cardiac arrhythmias. Atrial fibrillation (AF) after electrical injury is a rare manifestation. A 28-year-old man presented to the emergency department with palpitation after an electrical injury accident from a live wire carrying 220 volts in his home. He had loss of consciousness for 2 minutes after the accident, but was conscious at admission. He had no history of cardiovascular disease. Blood pressure was 130/80 mmHg, heart rate was 150 beats/min irregularly irregular, respiratory rate was 20 breaths/min, body temperature was 36.6oc, and oxygen saturation was 98% on room air. There was an entry wound on the palmar aspect of the right hand and exit wound on the plantar aspect of the right foot. Electrocardiogram showed AF with rapid ventricular response at 150 - 200 beats/min. Laboratory tests and echocardiogram were in normal limits. Pharmacologic cardioversion with intravenous amiodarone was given, followed by maintenance dose. AF was converted into sinus rhythm in 1 hour after amiodarone administration. The patient was discharged one day later. AF can occur after a low-voltage electrical injury. Cardiac monitoring for at least 24 hours is indicated in all patients with loss of consciousness, documented arrhythmias or ECG abnormalities, or who have sustained a high-voltage injury.